2010
DOI: 10.1007/s11804-010-1006-5
|View full text |Cite
|
Sign up to set email alerts
|

An essential solution of water entry problems and its engineering applications

Abstract: For solving water entry problems, a numerical method is presented, which is a CFD method based on free surface capturing method and Cartesian cut cell mesh. In this approach, incompressible Euler equations for a variable density fluid are numerically calculated by the finite volume method. Then artificial compressibility method, dual time-stepping technique and Roe's approximate Riemann solver are adopted in the numerical scheme. Finally, some application cases are designed to show the ability of the current m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…They found that the time from the impact of the cylinder on the water surface to the closure of the cavity under conditions with waves is longer than that under the no-wave condition. Wang et al [25,26] numerically simulated the vertical water entry process of a cylinder in regular waves and analyzed the influence of wave parameters on the hydrodynamic characteristics of the cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the time from the impact of the cylinder on the water surface to the closure of the cavity under conditions with waves is longer than that under the no-wave condition. Wang et al [25,26] numerically simulated the vertical water entry process of a cylinder in regular waves and analyzed the influence of wave parameters on the hydrodynamic characteristics of the cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Until the present paper, numerical methods to solve the variable-density artificialcompressibility equations have not been implemented on 3D unstructured meshes. They have been implemented on 2D structured meshes [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36], 3D structured meshes [17,37,38,39], and 2D unstructured meshes [40]. While most of these papers use the Cartesian cut-cell method to model simple obstacles, an implementation on 3D unstructured meshes is needed for more complex geometries.…”
Section: Introductionmentioning
confidence: 99%
“…W.-H. Wang and Y.-Y. Wang [16] simulated the physical process of a circular cylinder impacting on waves, and the response of lifting cable was obtained. Ryzhakov et al [17] used a Particle Finite Element Method (PFEM) for simulations of the sea-landing of an unmanned aerial vehicle (UAV).…”
Section: Introductionmentioning
confidence: 99%